Heart Rate in Hypertension: Review and Expert Opinion. (19th February 2019) - Dalal, Jamshed; Dasbiswas, Arup; Sathyamurthy, Immaneni; Maddury, Srinivasa Rao; Kerkar, Prafulla; Bansal, Sandeep; Thomas, Joy; Mandal, Sankar Chandra; Mookerjee, Soura; Natarajan, Sivakadaksham; Kumar, Viveka; Chandra, Nishith; et al.
Abstract : Heart rate (HR) is strongly associated with both peripheral and central blood pressures. This association has implications in hypertension (HTN) prognosis and management. Elevated HR in HTN further elevates the risk of adverse outcomes. Evidence suggests that HR is an independent risk factor for cardiovascular (CV) and total mortality in patients with HTN. With objective to engage physicians and researchers in India to identify and discuss the implications related to HR management in HTN, experts in the HTN management provided consensus recommendations. The key expert recommendations included the following. (i) Heart rate (HR) has inverse relationship with the central aortic pressure, whereby reduction in HR is associated with an increase in central aortic pressure. This counter-balances the benefit of HR reduction with the harmful effects of rising central aortic pressure. (ii) Increase in the resting HR is associated with increased risk of incident HTN. A linear association between the two is observed especially in individuals with HR >80 bpm. (iii) A reduced HR variability further adds to the propensity for the development of HTN, especially in men. (iv) Each 10 beats per minute increase in the resting HR can substantially increase the risk of adverse CV and mortality outcomes. On treatment HR provides a better prognostic guide. (v) Ambulatory HR with day-time and night-time HR evaluation may also suggest different impact on outcomes. (vi) Target HR in patients with HTN remains unclear. Generally, HR<70 bpm on beta blocker (BB) treatment is advised which may be further lowered in patients with comorbidities like heart failure and coronary artery disease. (vii) Adopting healthy lifestyle approaches to keep check on BP and HR is essential. (viii) Use selective beta-1 blocker in symptomatic cases with elevated HR beyond 80-85 mmHg. BBs are expected to benefit by lowering HR by nearly 10 bpm. Preference should be given to newer beta-blockers which reduce HR and both peripheral and central blood pressure to derive comprehensive advantage of this dual action. (ix) It still remains unclear whether reducing HR in HTN without comorbidities alters the CV and mortality outcomes.